Plasmid –mediated antimicrobial resistance bla CMY-2 gene and qnr (qnr A,qnr B and qnr S) genes in Salmonella isolated from human, animal and milk - Mohammed Khudor; Marwan Mohammed (Basrah Journal of Veterinary Research)
This study was conducted to detect the blaCMY-2 gene and qnr genes (qnrA, qnrB and qnrS)in Salmonella isolates from 278 different samples (50 direct milk samples, 50 indirect milksamples, 50 feces samples, 50 teat swab samples, 28 manual milk swabs and 50 stoolsamples) in Basrah province. The results showed that the percentage of Salmonella isolatesin the samples was 6.1% by using API system and by PCR technique for identification. Thehighest resistance to Salmonella isolates were found against chloramphenicol and rifampin(100%). While all isolates were sensitive to ciprofloxacin . The use of plasmid treatment(Plasmid curing) by temperature method showed that 41.1% of total Salmonella isolateswere associated with antimicrobial resistance of the plasmid. Plasmid analysis by moleculardetection revealed that 11 isolates (64.7%) was positivity for blaCMY-2 while the qnrquinolone gene (A, B and S) was not detected in the isolates